Body mass index and blood pressure: a study among high school students - Kuncheria, Jo Martin; George, Jeethu; Rozario, Cyril Ignatius (International Journal of Contemporary Pediatrics, 2023)
Background: Hypertension and its associated risk factors like overweight and obesity begins in childhood but it goes undetected. Revealing any relation between overweight/obesity and high blood pressure and its magnitude will help the policy makers in planning and implementation of necessary interventions. Objectives were to find a relation between Blood pressure and body mass index among high school children, to estimate the prevalence of high blood pressure in the study population and to estimate the prevalence of overweight and obesity in the study population. Methods: A cross sectional study among students of 8th, 9th, 10th standards (n=697) of two randomly selected Government High School was conducted. Data was collected using a semi-structured questionnaire. Anthropometric measurements and Blood pressure were measured. Data was analyzed using SPSS software version 16. Results: Elevated Blood pressure was detected in 4.7% and none of the participants had hypertension. The prevalence of obesity and overweight were 7% and 19.8% respectively. A positive significant correlation was seen between BMI and systolic blood pressure (r = 0.171, p=0.001) as well as between BMI and diastolic blood pressure (r= 0.094, p 0.013). Both elevated BP and overweight/obesity were significantly higher in students who had previous COVID infection, Junk food consumption and less physical activity. Conclusions: Prevalence of Obesity and elevated BP were found to be high among male children. Systolic Blood pressure showed significant positive correlation with Body Mass Index irrespective of gender. Positive correlation was seen between BMI and Diastolic blood pressure but found to be significant in males only.